The effectiveness of dance interventions on the cognitive functioning of people with dementia or cognitive impairment: A systematic review - Dauda Salihu; Surajo Kamilu Sulaiman; Umar Muhammad Bello; Osama Mohamed Elsayed Ramadan; Hadiza Yahaya; Muhammad Chutiyami (Nursing Practice Today)
Background & Aim: Dementia significantly impair cognitive abilities, well-being, and the functioning of daily life, but there is no cure yet. In the search for non-pharmacological interventions, dance has emerged as a potential complementary therapy to support people with dementia or cognitive impairment. The aim of this study is to investigate the effectiveness of various dance interventions on the cognitive performance of people with dementia or cognitive impairment. Methods & Materials: In accordance with the PRISMA 2020 guidelines, a systematic search was conducted in six databases (APA-PsycINFO, Web of Science, Medline, CINAHL, Embase, and Cochrane)from 2002 to 2023. The quality of the studies was rigorously assessed using the JBI tool. A narrative synthesis approach was used to summarize the findings. Effects of the interventions were presented either as Standardized Mean Difference (SMD), Weighted Mean Difference (WMD), or Mean Difference (MD). An effect size of < 0.1 is considered trivial, 0.1-0.3 is small while > 0.5 is interpreted as a large effect. Results: The systematic results showed significant improvements in global cognition (SMD= 0.54 to 6.10), memory (SMD= 0.24 to 0.56), attention (SMD= 0.38), and language and fluency (SMD=0.61) in different dance genres such as ballroom, Latin and aerobics. However, different effects were observed in executive and visuospatial functions. Conclusion: This systematic-review shows the effectiveness of dance interventions in improving several cognitive functions in people with dementia, including memory, attention, language, and fluency. This study supports the use of dance as an effective non-pharmacological approach in dementia care and merits its consideration in treatment strategies and further research studies.